Rekonstruksi konsep dasar ilmu pendidikan Islam dalam Al-Quran di tengah dekadensi moral pada era society 5.0 - Arjuna, Arjuna; Kurahman, Opik Taupik; Rusmana, Dadan; Maulana, Hadi (Al-Liqo: Jurnal Pendidikan Islam, 2024)
This study aims to analyze the reconstruction of the basic concept of Islamic education in the Qur'an in addressing moral decadence in the era of Society 5.0. Using a qualitative approach, this article draws on various references, including books and articles, as supporting data (library research). The data analysis technique employed is content analysis. In the current era, Islamic education must implement the fundamental concepts outlined in the Qur'an to equip students with a solid foundation to face the challenges of Society 5.0. The findings reveal that the reconstruction of the basic concept of Islamic education in the Qur'an for the Society 5.0 era includes: first, addressing moral decadence in the modern context; second, integrating Islamic values in digital education; third, contextual character education; fourth, problem-based learning; fifth, strengthening social and emotional skills; and sixth, collaboration between technology and spiritual values. With a strong foundation in faith and morals, students will be better equipped to maintain their integrity in a changing world. Education should go beyond measuring student abilities and focus on guiding them to act according to Islamic values and ethics as outlined in the Qur'an.